Fenomena Menggadaikan Barang Pada Mahasiswa Perantau Asal Manggarai di Malang dalam Perspektif Teori Habitus Pierre Bourdieu - Nafrianus Sunggung; Winin Maulidya Saffanah (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
The phenomenon of pawning belongings among students living away from home is a survival strategy in the face of economic constraints. This study aims to understand the practice of pawning among students from Manggarai living in Malang City using Pierre Bourdieu’s theoretical perspective. This study employs a descriptive qualitative approach, utilizing data collection techniques through in-depth interviews with seven informants, supplemented by observation and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results indicate that pawnbroking is generally carried out by pledging items of high economic value. The main factors driving this practice are economic constraints and urgent needs to meet basic necessities. Pawnbroking is chosen because it is considered a quick solution, although it has the potential to lead to financial dependence. From Bourdieu’s perspective, this practice is the result of the interaction between habitus, economic capital, and social capital within the context of migrant life.